Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.4067/s0717-95022009000400026
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Histological Study of the Tongue of Rat (Rattus Norvegicus), Bat (Eidolon Helvum) and Pangolin (Manis Tricuspis)

Abstract: This study assessed the micro anatomical differences in the tongue of rat, bat and pangolin with a view to establishing the functional anatomical differences of these mammalian tongues on their dietary pattern. Ten rats, ten bats and ten pangolins were used for this study. The animals were sacrificed and the tongue excised and processed for light microscopical study adopting the following stains: Haematoxylin Eosin, Verhoeff Gieson and Masson trichrome. The results showed non papillation of the keratinized str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 15 publications
3
41
0
1
Order By: Relevance
“…As in the previous published data, the lingual papillae were species-specific, in which differing in their number among mammalian species, these differences may depend on dissimilarities in diet, feeding habits and handling of food in mouth (Emura et al, 2002b;Abumandour & El-Bakary), the previous data clear in; our study in Egyptian fruit bat, this confirmed by presence of four types of lingual papillae; two mechanical and two gustatory as noted in; bats (Selim et al, 2008;Abumandour & El-Bakary;Abayomi et al, 2009), moreover other mammals have four lingual papillae; as in our study in New Zealand white rabbits; one mechanical (filiform) and three gustatory (fungiform, foliate and circumvallate) as noted in; rats (Nasr et al, 2012), bank vole (Jackowiak & Godynicki, 2005), dog and fox (Emura et al, 2006). However, three types of lingual papillae; one mechanical (filiform) and two gustatory (fungiform and circumvallate) as noted in; bats (Pastor et al, 1993;Emura et al, 2001b;Park & Lee, 2009;Masuko et al, 2007), however, there were two types only of papillae (filiform and fungiform) in hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 79%
“…As in the previous published data, the lingual papillae were species-specific, in which differing in their number among mammalian species, these differences may depend on dissimilarities in diet, feeding habits and handling of food in mouth (Emura et al, 2002b;Abumandour & El-Bakary), the previous data clear in; our study in Egyptian fruit bat, this confirmed by presence of four types of lingual papillae; two mechanical and two gustatory as noted in; bats (Selim et al, 2008;Abumandour & El-Bakary;Abayomi et al, 2009), moreover other mammals have four lingual papillae; as in our study in New Zealand white rabbits; one mechanical (filiform) and three gustatory (fungiform, foliate and circumvallate) as noted in; rats (Nasr et al, 2012), bank vole (Jackowiak & Godynicki, 2005), dog and fox (Emura et al, 2006). However, three types of lingual papillae; one mechanical (filiform) and two gustatory (fungiform and circumvallate) as noted in; bats (Pastor et al, 1993;Emura et al, 2001b;Park & Lee, 2009;Masuko et al, 2007), however, there were two types only of papillae (filiform and fungiform) in hematophagous bats (Masuko et al).…”
Section: Discussionsupporting
confidence: 79%
“…In addition to capturing and manipulating foods, which are functions of the lingual papillae, the fungiform and circumvallate papillae facilitate taste of food (Kilinc et al 2010). Abayomi et al (2009) stated that the conical and crownlike structure of papillae observed in fruit bats suggest their function in food retention when flying. The papillae projections may be for gripping on food and scraping on fruits when feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The papillae projections may be for gripping on food and scraping on fruits when feeding. The high abundance and increase in surface area of these enlarged papillae are most likely to assist in oral absorption (Abayomi et al 2009) and efficient transport of food, particularly a liquid diet, toward the pharynx and consequently increasing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…There are four types of papillae identified on the mammalian tongue; circumvallate, fungiform and foliate papillae with taste buds, and filiform papillae without taste buds . The anterior region of Wistar albino rat's tongue dorsum contains two types of papillae: filiform and fungiform papillae, while few circumvallate papillae are seen in the posterior region of the tongue; (Karakoç et al.,). The number of circumvallate papillae varies from none to fourteen among the different species of mammals, and the Wistar albino rat is characterized by the presence of a solitary circumvallate papilla .…”
Section: Introductionmentioning
confidence: 99%